Epidurolysis is a Promising Treatment for Stage I-II Lumbar Disc Herniation at the Three-Month Follow-Up - Trianggoro Budisulistyo (Lumina : Indonesian Journal of Neurology, 2026)
Introduction: About 90% of patients with lumbar disc herniation (LDH) improve with conservative treatment, while 10–19% require surgery. Epidural steroid injection (ESI) with local anesthetic provides pain relief for up to 6 months (30–40%) and up to 1 year (68.5%). Epidurolysis, using 1500 units of hyaluronidase before ESI, is often applied in patients who continue to experience pain after spinal surgery. This study compares pain intensity and activities of daily living (ADL) in Stage I–II LDH patients treated with either epidurolysis or ESI. Methods: This experimental study used a pre- and post-test control group design. Patients with Stage I–II LDH at Dr. Kariadi Hospital, Semarang, were divided into two groups: epidurolysis and ESI. NRS, Pain DETECT, and ODI scores were evaluated before treatment, at Week 3, and at Month 3, then compared across observation times. Results: From January to August 2022, 161 patients met the inclusion criteria: 84 received epidurolysis and 77 received ESI. Eighteen participants dropped out. Significant improvements in NRS, Pain DETECT, and ODI scores were observed up to Month 3 (p < 0.05). The epidurolysis group showed greater improvement, with lower NRS (1.21 ± 0.50 vs 1.51 ± 0.53), Pain DETECT (8.61 ± 2.66 vs 12.17 ± 2.78), and ODI (4.72 ± 3.34 vs 8.51 ± 3.67) scores. Demographic factors had no significant effect on ADL changes. Conclusion: Hyaluronidase reduces fibrosis and edema, enhances triamcinolone absorption, and may improve nerve recovery. Adding 1500 units of hyaluronidase before ESI results in better pain relief and functional outcomes in Stage I–II chronic LDH patients. Keywords: Stage I-II LDH, Triamcinolone, Hyaluronidase, NRS, Pain DETECT, ODI